Laminar flame characteristics of THF family fuels at elevated temperatures and pressures. (1st August 2020) - Wang, Xibin; Chen, Rixin; He, Benzhuang; Li, Dehua; Qin, Mingyuan; Fan, Xiangshan
Abstract: Laminar flame characteristics of THF family fuels, including tetrahydrofuran (THF), 2-methyltetrahydrofuran (MTHF) and 2, 5-dimethyltetrahydrofuran (DMTHF), were studied in constant volume bomb using high-speed schlieren photography technique under the conditions of initial pressure of 1–4 bar, initial temperature of 373–453 K and equivalence ratio of 0.7–1.6. The nonlinear extrapolation method was used to obtain the laminar burning velocity and Markstein length. The results showed that laminar burning velocities of the three fuels vary with equivalence ratio and reached their peak value at equivalence ratio near 1.1, and are accelerated with the elevated initial temperature and decelerated with the elevated initial pressure. The relationship of laminar burning velocity among the three fuels is THF > MTHF > DMTHF. The difference of the velocity is mainly due to the adiabatic flame temperatures and thermal diffusivity which are THF > MTHF > DMTHF and THF≈MTHF > DMTHF respectively. Quantitative analysis indicates that the laminar burning velocity is positive exponential power function with initial temperature and negative exponential power function with initial pressure. The laminar burning velocities of the three fuels are more sensitive to the variation of both initial temperature and pressure for fuel-lean mixtures, and MTHF is the most sensitive among the three fuels. Flame instability among the three fuels is THF≈MTHF > DMTHF, because the relationship of the effective Lewis number and flame thickness is THF < MTHF < DMTHF, meaning that the diffusion-thermal instability among the three fuels is THF > MTHF > DMTHF.